2012
DOI: 10.1002/jccs.201200169
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Complexes of Unsymmetrical Schiff Bases Derived from Ethylenediamine and o‐Hydroxyaldehyde/Ketone and Their Anti‐microbial Evaluation

Abstract: The titanium(IV) complexes of the unsymmetrical Schiff base ligands (L) of ethylenediamine and salicylaldehyde, o‐hydroxyacetophenone, o‐hydroxynapthaldehyde have been prepared and characterized when unsymmetrical ligands are synthesized through in situ partial displacement of the symmetrical bis‐Schiff bases. Compounds have been characterized by elemental analysis, electronic, (Infra‐red) IR, 1H NMR spectral data, magnetic susceptibility measurement and molar conductance and eight coordinated geometry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The molar conductance values of the prepared zirconium (IV) complexes of the N, N′-bis (isatin) diamine schiff base ligands found very low which is depicted in Table I. The low molar conductivity of all complexes suggest their non-electrolytic character (Uddin et al 2012). This revealed that all ligands were covalently bonded with zirconium.…”
Section: Molar Conductancementioning
confidence: 93%
See 1 more Smart Citation
“…The molar conductance values of the prepared zirconium (IV) complexes of the N, N′-bis (isatin) diamine schiff base ligands found very low which is depicted in Table I. The low molar conductivity of all complexes suggest their non-electrolytic character (Uddin et al 2012). This revealed that all ligands were covalently bonded with zirconium.…”
Section: Molar Conductancementioning
confidence: 93%
“…1 and 2, respectively. The spectra of the ligands should contain stretching bands for the azomethine group ((>C=Ngroup), C-N and C=O bonds at 1625-1582 cm -1 (Singh et al, 2012), 1020-1250 cm -1 (Uddin et al, 2012) and 1730-1750 cm -1 (Konstantinovic et al, 2015) regions, respectively. The vibrational frequency at 3150-3300 cm -1 (Ade et al, 2012) and 1460 cm -1 (Konstantinović et al, 2015) correspond stretching and bending vibration of N-H bond.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…The band for the C-N stretching frequency literally assigned in the region 1250-1020 cm -1 ( Uddin et al 2012). In the present work, the existence of peak at 1203.58 cm -1 , 1203.58 cm -1 and 1209.37 cm -1 showed the existence of the C-N stretching frequency in the ligands L 1 , L 2 ,L 3 , respectively and 1199.72 cm -1 , 1201.65cm -1 and 1201.65 cm -1 for complexes MoO 2 L 1 , MoO 2 L 2 and MoO 2 L 3 , respectively.…”
Section: Ftir Spectral Studymentioning
confidence: 99%
“…In a multitude of coordination compounds, titanium predominantly assumes the 4+ oxidation state. This is accomplished through oxo‐titanium (IV), TiO 2+ configuration, or non‐oxotitanium (IV), Ti 4+ ions formed by the loss of all 4s and 3d electrons 31,32 . Ti (IV) complexes have been extensively explored for their potential in antitumor, antimicrobial, anti‐coronavirus (SARS‐CoV‐2), and anticancer activities 33–36 .…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished through oxo-titanium (IV), TiO 2+ configuration, or non-oxotitanium (IV), Ti 4+ ions formed by the loss of all 4s and 3d electrons. 31,32 Ti (IV) complexes have been extensively explored for their potential in antitumor, antimicrobial, anti-coronavirus (SARS-CoV-2), and anticancer activities. [33][34][35][36] Titanocene dichloride and budotitane have successfully advanced to clinical trials, attributed to their cytotoxic potency and selectivity.…”
Section: Introductionmentioning
confidence: 99%